Simulacrum and its representations in industrial design (Al-Academy, 2025)
The research deals with the concept of simulacrum and its impact on industrial design within the context of postmodern philosophies, where the simulacrum appeared as a free copy of the original that challenges the concepts of traditional copies and realistic representation. The research reviews the development of the concept starting from its roots in Platonic philosophy, through its developments in the writings of postmodern philosophers. The research focuses on the applications of simulacrum in modern industrial design, indicating how it is used to redefine aesthetic identity and discusses the relationship between beauty and ugliness within the framework of simulacrum, where ugliness is integrated as an aesthetic element, opening new horizons for creativity and diversity in industrial designs. The research question was as follows: How to employ the concept of simulacrum and its representations in industrial design? The researcher reached the results after analyzing the samples according to the analysis form based on the indicators of the theoretical framework, the most important of which was that simulacrum in industrial design provides creative solutions that challenge traditional patterns, and designs based on simulacrum provide a unique and unexpected sensory experience